The Roman Catholic conceptualisation of morality: Its essence and distinctive character - Pope, Stephen J. (Verbum et ecclesia, 2024)
Over the course of its history Catholicism has generated several different conceptions of morality. The early medieval church conceived morality primarily in terms of caritas and other virtues, the modern church generated a legalistic conception of morality, and the post-Vatican II church proposes a relational conception of morality. Intradisciplinary and/or interdisciplinary implications: The essence of morality concerns natural virtues and natural moral law, which all people of goodwill can grasp, appreciate, and act upon. The distinctive conception of morality is identified with our ultimate end, the beatific vision, the theological virtues, and the ethics of discipleship centred on caritas.